2021
DOI: 10.1093/ptj/pzab028
|View full text |Cite
|
Sign up to set email alerts
|

Custom Dynamic Orthoses and Physical Therapist Intervention for Bilateral Midfoot Amputation: A Case Report

Abstract: Objective Partial foot amputation (PFA) is often associated with decreased mobility and function. Recent advances in custom carbon-fiber dynamic ankle-foot orthoses (CDO) have improved gait, pain, and function following musculoskeletal trauma and may benefit individuals with PFA. However, limited information is available related to CDO use outside the military. The purpose of this case report is to describe the course of care and outcomes of a civilian provided CDOs after bilateral transmetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…[3][4][5][6][7] Limited data are available to suggest similar outcomes can be obtained in a civilian setting. 8 In 2013, a novel CDO and complimentary care program was developed to meet the needs of civilians. Previous research has shown a beneficial effect of a sports medicine-based rehabilitation program in conjunction with CDOs, resulting in improved performance and reduced pain.…”
Section: Background and Significancementioning
confidence: 99%
“…[3][4][5][6][7] Limited data are available to suggest similar outcomes can be obtained in a civilian setting. 8 In 2013, a novel CDO and complimentary care program was developed to meet the needs of civilians. Previous research has shown a beneficial effect of a sports medicine-based rehabilitation program in conjunction with CDOs, resulting in improved performance and reduced pain.…”
Section: Background and Significancementioning
confidence: 99%
“…의족을 사용함으로써 기능을 보상하고 절단으 로 인한 미용적 문제를 해결하여, 신발을 정상적으로 착용하고 편안 한 보행 형태를 보전할 수 있다 [39,40]. 입각기 후반 기능을 보상하기 위해 단하지 보조기 형태의 의족을, 원위 중족부 압력을 감소시키기 위하여 흔들의자바닥 형태의 바닥재를 흔히 사용한다 [40,41].…”
Section: 열 절단 열 절단 수술 후 남은 발의 보호와 균형 그리고 압력 분산을 위해서 맞춤 제작 깔창(Insole)이...unclassified